Digital Electronics : Principles and Applications - Tokheim, Roger L.; Hoppe, Patrick E. (McGraw-Hill, 2022)
"Digital Electronics, Principles and Applications, ninth edition, is an easy-to-read introductory text for students new to the field of digital electronics. Providing entry-level knowledge and skills for a wide range of occupations is the goal of this textbook and its ancillary materials"